Simulation, design of unequal five way wilkinson power divider for EW applications - Siva Charan, M; Vummadisetty. Naidu, Praveen; Rajasekhar, A; Bansod, Gaurav; Raveendra, P; Kumar, Arvind (International Journal of Engineering and Technology, 2018)
This paper deals with the design and simulation of unequal 5-way Wilkinson power divider used for Electronic Warfare (EW) applications. The frequency range of operation intended for this design is 6 GHz to 18 GHz. The proposed Wilkinson power divider is designed on a low cost FR-4 substrate having height of 1.5mm, relative permittivity of 4.4 and loss tangent of 0.02. The design occupies a size of 11mm x 33 mm x 1. 5 mm. Equal split Wilkinson power dividers are utilized for implementation of this design. High isolation has been obtained throughout the frequency range of 6 GHz to 18 GHz. The design procedure is discussed. The simulated results are presented by using ADS simulation software.Â Â Â